2016
DOI: 10.1074/jbc.m115.697599
|View full text |Cite
|
Sign up to set email alerts
|

Negative Feed-forward Control of Tumor Necrosis Factor (TNF) by Tristetraprolin (ZFP36) Is Limited by the Mitogen-activated Protein Kinase Phosphatase, Dual-specificity Phosphatase 1 (DUSP1)

Abstract: Background: ZFP36 negatively regulates AU-rich element-containing mRNAs. Results: DUSP1 silencing increases ZFP36 expression and enhances negative feed-forward control of TNF. Conclusion: MAPK inhibition initially attenuates TNF mRNA, but reduced feed-forward control subsequently produces an increase. Significance: Understanding such networks is essential to develop novel anti-inflammatory therapies or understand TNF repression by glucocorticoids, which may not require DUSP1 or ZFP36 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 65 publications
4
30
0
Order By: Relevance
“…After 1 h of IL1B, DUSP1 protein was induced, and this was enhanced by dexamethasone ( Fig. 10A) (22,23,27). In previous studies dexamethasone, IL1B, and IL1B plus dexamethasone showed no effect on the expression of total ERK (22) and total p38 (36), and Western blotting for total JNK also confirms this for JNK (data not shown).…”
Section: Effect Of Dusp1 Silencing On Mapks Irf1supporting
confidence: 70%
See 2 more Smart Citations
“…After 1 h of IL1B, DUSP1 protein was induced, and this was enhanced by dexamethasone ( Fig. 10A) (22,23,27). In previous studies dexamethasone, IL1B, and IL1B plus dexamethasone showed no effect on the expression of total ERK (22) and total p38 (36), and Western blotting for total JNK also confirms this for JNK (data not shown).…”
Section: Effect Of Dusp1 Silencing On Mapks Irf1supporting
confidence: 70%
“…Turning to the actions of dexamethasone, we confirm that IL1B-induced expression of DUSP1 is enhanced by dexamethasone to reduce MAPK phosphorylation (23,27) (Fig. 12C).…”
Section: Negative Regulation Of Irf1 By Mapkssupporting
confidence: 59%
See 1 more Smart Citation
“…2C, panel i). Thus, in A549 cells, DUSP1 silencing transiently hyper-activates IL1B-induced MAPKs and correspondingly increases ZFP36 expression (63) (Fig. 2C, panel ii).…”
Section: Incoherent Feedforward Control By Zfp36mentioning
confidence: 85%
“…ZFP36 induction occurs in many cells, including A549 epithelial and primary human airway smooth muscle cells (61,62). This requires p38 MAPK to constitute an incoherent feedforward loop with ZFP36 as a negative regulator of ARE-containing mRNAs, such as TNF (60,63) (Fig. 2C, panel i).…”
Section: Incoherent Feedforward Control By Zfp36mentioning
confidence: 99%